BS ISO 23678-2. Service personnel for the maintenance, thorough examination, operational testing, overhaul and repair of lifeboats (including free-fall lifeboats) and rescue boats (including fast rescue boats), launching appliances and release gear. Part 2. Service personnel initial training (17th August 2021) - British Standards Institution,
No abstract available